Metody aktuarialne w programach studiów na kierunku Finanse i Bankowość Wydziału Zarządzania i Informatyki Akademii Ekonomicznej we Wrocławiu - Ronka-Chmielowiec, Wanda (Actuarial Methods in Finance and Banking Programme Study of Management and Computer Science Faculty At Wroclaw University of Economics, 2006)
In the article it was presented didactics experiences from many years concern mathematical methods applications in insurance courses for students of finance and banking. These courses have specialists character and are lectured on such specialisms as: banking and insurance, finance management and risk management. Among many insurance subjects in management and computer science faculty program, there are some which include actuarial mathematics problems such as:• Actuarial methods,• Risk management in insurance,• Non-life insurance,• Life insurance and pension systems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 155-163